Impacts of Drinking Water Quality on Housing Prices - Huang, Huili (Transactions on Computer Science and Intelligent Systems Research, 2024)
Real estate and the housing market are vital for the U.S. economy, with factors such as economic growth, interest rates, government policies, and subsidies influencing housing prices. This paper will be focusing on the drinking water quality on housing prices by employing the existing researches of different methodologies. Hedonic property value analysis and production function have been used to assess the worth of environmental assets. One research has developed a household production function model that demonstrates that the economic value of system enhancements depends on the costs incurred by households in treating piped water, the availability of alternative options, and the feasibility of relocation. Another residential sorting model was adapted to identify variables influencing the relationship between piped water quality and house price. A natural experiment design found that land and property values increase in close proximity to unpolluted water bodies compared to polluted ones. The significance of this paper is to provide valuable insights for both homeowners and policymakers, as well as to help in making informed decisions regarding infrastructure development and urban planning to ensure access to safe and clean drinking water for all residents.